The Kejadian Pertama Rabbit Haemorrhagic Disease Berdasarkan Studi Seroprevalensi di Provinsi Jawa Barat, Indonesia - Setyaningsih, Retno; Wibawan, I Wayan Teguh; Setiyaningsih, Surachmi; Handharyani, Ekowati; Murtini, Sri; Biharidin, Ahmad (Jurnal Veteriner; Vol 23 No 3 (2022), 2022)
Rabbit Haemmorhagic Disease (RHD) is one of viral diseases in rabbits that is still exotic in Indonesia. The RHD disease is caused by the Rabbit Haemorrhagic Disease Virus (RHDV) which is a calicivirus of the genus Lagovirus, Caliciviridae family. The high genetic variation of the RHDV and the rapid spread have the potential to disrupt rabbit farm (rabbittery) production and trade activities, especially rabbit exports, which require clarity on the status and situation of RHD disease in rabbits in Indonesia. A case of suspected RHD in Indonesia was first detected in the Philippines where rabbits exported from Indonesia were detected to be seropositive to RHD which resulted in rabbit export activities to the country was stopped. There is no data on the presence of RHD disease in rabbits in Indonesia, so the seroprevalence study is useful to provide preliminary information on the presence of this disease in Indonesia. This study was conducted on 163 rabbits samples raised in the Lembang area, Bandung, West Java, which is known as the largest rabbit farming center in Indonesia. Rabbit samples were taken at rabbit farms spread across seven villages namely Lembang, Pagerwangi, Cikahuripan, Cikole, Sukajaya, Gudangkahuripan and Jambudipa. The rabbits serum samples obtained were tested using the Indirect Enzym Linked Immunosorbant Assay (ELISA) method to determine the titer of antibodies against RHD. Based on the results of the analysis, it is known that 120 out of 163 rabbit serum samples showed positive antibody titers against RHD.  The presence of antibody titers in rabbits on such farms can be preliminary information to be able to carry out further studies.